Praktek Ijon Petani Pemilik Lahan Sawah; Perspektif Agen-Struktur - Azuz, Faidah; Nonci, Nurmi; Iskandar, Abdul Malik; Bachri, Syamsul; Masdar, Muhammad; Harifuddin, Harifuddin; Azuz, Fidaan Husein (Sodality: Jurnal Sosiologi Pedesaan, 2023)
The status of farmers in the socio-economic study of agriculture referring to land ownership consists of landowner farmer, tenant farmer, and sharecropper. Landowner farmer holds the highest position. Many landowner farmers have been trapped in “Ijon” practice for years, which makes them work on their own land to pay their debts for a long period of time. The purpose of this study is to find out the background of farmers who were involved in the ijon practice, the reasons behind their entanglement in the ijon practice, the uses of loans, and how the loans were paid. The study location was village of XYZ in East Nusa Tenggara Province, involving 22 farmers who were involved in the practice of ijon. This study used a qualitative analysis of agency structure from Gidden’s perspective. This paper concludes that farmers were involved in the ijon practice to meet urgent non-productive needs. Most of the farmers’ earnings are used to pay debts. Farmers who are trapped in the ijon system for a long period of time will bear the status of “the landowner farmers who work as farm laborers on their own land.” This status has yet to be categorized in the agricultural economic approach.